2021
DOI: 10.1167/tvst.10.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality–Based and Conventional Visual Field Examination Comparison in Healthy and Glaucoma Patients

Abstract: Purpose Clinically evaluate the noninferiority of a custom virtual reality (VR) perimetry system when compared to a clinically and routinely used perimeter on both healthy subjects and glaucoma patients. Methods We use a custom-designed VR perimetry system tailored for visual field testing. The system uses Oculus Quest VR headset (Facebook Technologies, LLC, Bern, Switzerland), that includes a clicker for participant response feedback. A prospective, single center, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Smartphone-based head-mounted perimeters were later introduced in 2017 and 2018 and showed promising results [ 3 , 9 , 10 ]. Perimeters based on VR technique were developed rapidly in recent years [ 11 , 12 , 13 , 14 ]. Another study using the Oculus Quest VR headset to simulate a standard visual field test was compared with the Octopus 900 and showed that the performance of the two was comparable [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphone-based head-mounted perimeters were later introduced in 2017 and 2018 and showed promising results [ 3 , 9 , 10 ]. Perimeters based on VR technique were developed rapidly in recent years [ 11 , 12 , 13 , 14 ]. Another study using the Oculus Quest VR headset to simulate a standard visual field test was compared with the Octopus 900 and showed that the performance of the two was comparable [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perimeters based on VR technique were developed rapidly in recent years [ 11 , 12 , 13 , 14 ]. Another study using the Oculus Quest VR headset to simulate a standard visual field test was compared with the Octopus 900 and showed that the performance of the two was comparable [ 13 ]. In their study, correlation coefficients were 0.77, 0.50, and 0.70 for all, healthy, and glaucoma patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of tests are conducted every day. Although there have been many interesting advances in perimetry ( Greenfield, Deiner, Nguyen, Wollstein, Damato, Backus, Wu, Schuman, & Ou, 2022 ; Jones, 2020 ; Prager, Kang, & Tanna, 2021 ; Prince, Thompson, Mwanza, Tolleson-Rinehart, & Budenz, 2021 ; Stapelfeldt, Kucur, Huber, Höhn, & Sznitman, 2021 ; Turpin, Myers, & McKendrick, 2016 ), the community pursuing clinical visual field research remains relatively small. To many newcomers, perimetry first appears as something of a black art, with a specialist terminology somewhat at odds with mainstream psychophysics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, though electronics are developing at a rapid rate, there remain technical limitations on how luminance is translated to bits on a monitor. 16 At the high end of the logarithmic dB range (very dim stimulus), it is nearly impossible to distinguish the low luminance values with adequate confidence intervals. 17 For example, a 30-dB diminution of a standard 255-bit stimulus target requires the illumination of less than a single (0.25) bit.…”
Section: Irtual R Eality P Erim...mentioning
confidence: 99%